Routine scale and polish for periodontal health in adults - Worthington, Helen V; Clarkson, Jan E; Bryan, Gemma; Beirne, Paul V (Cochrane database of systematic reviews, 2013)
Many dentists or hygienists provide scaling and polishing for patients at regular intervals, even if those patients are considered to be at low risk of developing periodontal disease. There is debate over the clinical effectiveness and cost effectiveness of 'routine scaling and polishing' and the 'optimal' frequency at which it should be provided for healthy adults.A 'routine scale and polish' treatment is defined as scaling or polishing or both of the crown and root surfaces of teeth to remove local irritational factors (plaque, calculus, debris and staining), that does not involve periodontal surgery or any form of adjunctive periodontal therapy such as the use of chemotherapeutic agents or root planing. The objectives were: 1) to determine the beneficial and harmful effects of routine scaling and polishing for periodontal health; 2) to determine the beneficial and harmful effects of providing routine scaling and polishing at different time intervals on periodontal health; 3) to compare the effects of routine scaling and polishing with or without oral hygiene instruction (OHI) on periodontal health; and 4) to compare the effects of routine scaling and polishing provided by a dentist or dental care professional (dental therapist or dental hygienist) on periodontal health. We searched the following electronic databases: the Cochrane Oral Health Group's Trials Register (to 15 July 2013), CENTRAL (The Cochrane Library 2013, Issue 6), MEDLINE via OVID (1946 to 15 July 2013) and EMBASE via OVID (1980 to 15 July 2013). We searched the metaRegister of Controlled Trials and the US National Institutes of Health Clinical Trials Register (clinicaltrials.gov) for ongoing and completed studies to July 2013. There were no restrictions regarding language or date of publication. Randomised controlled trials of routine scale and polish treatments (excluding split-mouth trials) with and without OHI in healthy dentate adults, without severe periodontitis. Two review authors screened the results of the searches against inclusion criteria, extracted data and assessed risk of bias independently and in duplicate. We calculated mean differences (MDs) (standardised mean differences (SMDs) when different scales were reported) and 95% confidence intervals (CIs) for continuous data and, where results were meta-analysed, we used a fixed-effect model as there were fewer than four studies. Study authors were contacted where possible and where deemed necessary for missing information. Three studies were included in this review with 836 participants included in the analyses. All three studies are assessed as at unclear risk of bias. The numerical results are only presented here for the primary outcome gingivitis. There were no useable data presented in the studies for the outcomes of attachment change and tooth loss. No studies reported any adverse effects.- Objective 1: Scale and polish versus no scale and polish Only one trial provided data for the comparison between scale and polish versus no scale and polish. This study was conducted in general practice and compared both six-monthly and 12-monthly scale and polish treatments with no treatment. This study showed no evidence to claim or refute benefit for scale and polish treatments for the outcomes of gingivitis, calculus and plaque. The MD for six-monthly scale and polish, for the percentage of index teeth with bleeding at 24 months was -2% (95% CI -10% to 6%; P value = 0.65), with 40% of the sites in the control group with bleeding. The MD for 12-monthly scale and polish was -1% (95% CI -9% to 7%; P value = 0.82). The body of evidence was assessed as of low quality.- Objective 2: Scale and polish at different time intervals Two studies, both at unclear risk of bias, compared routine scale and polish provided at different time intervals. When comparing six with 12 months there was insufficient evidence to determine a difference for gingivitis at 24 months SMD -0.08 (95% CI -0.27 to 0.10). There were some statistically significant differences in favour of scaling and polishing provided at more frequent intervals, in particular between three and 12 months for the outcome of gingivitis at 24 months, with OHI, MD -0.14 (95% CI -0.23 to -0.05; P value = 0.003) and without OHI MD -0.21 (95% CI -0.30 to -0.12; P value < 0.001) (mean per patient measured on 0-3 scale), based on one study. There was some evidence of a reduction in calculus. This body of evidence was assessed as of low quality.- Objective 3: Scale and polish with and without OHIOne study provided data for the comparison of scale and polish treatment with and without OHI. There was a reduction in gingivitis for the 12-month scale and polish treatment when assessed at 24 months MD -0.14 (95% CI -0.22 to -0.06) in favour of including OHI. There were also significant reductions in plaque for both three and 12-month scale and polish treatments when OHI was included. The body of evidence was once again assessed as of low quality.- Objective 4: Scale and polish provided by a dentist compared with a dental care professionalNo studies were found which compared the effects of routine scaling and polishing provided by a dentist or dental care professional (dental therapist or dental hygienist) on periodontal health. There is insufficient evidence to determine the effects of routine scale and polish treatments. High quality trials conducted in general dental practice settings with sufficiently long follow-up periods (five years or more) are required to address the objectives of this review.